Cabin management and ventilation strategies for improved indoor environmental quality in passenger vehicles of developing tropics - John Omomoluwa Ogundiran; Jean-Paul Kapuya Bulaba Nyembwe; James Ogundiran; Vaibhav C. Gandhi; Anabela Ribeiro; Manuel Gameiro da Silva (Results in Engineering)
Ensuring adequate Indoor Environmental Quality (IEQ) in passenger vehicles is essential for safeguarding commuters’ health, comfort, and safety. This is particularly true in developing tropical regions (DTs), where higher commuter density, inadequate infrastructure, poor vehicle maintenance, extreme climatic conditions, and the absence of IEQ regulations form a set of conditions that exacerbate public health risks. The current study aimed to evaluate indoor air quality, thermal comfort, and ventilation performance in public transport vehicles in Lagos and to develop pragmatic improvement strategies. It examines the IEQ conditions in Nigeria's public transportation system, specifically focusing on Bus Rapid Transit (BRT) buses, light rail (LR), and intercity trains in Lagos. A mixed-methods approach was employed, mixing real-time measurements of key parameters, including temperature, humidity, concentrations of CO₂, PM2.5, PM10, and sound pressure level, collected during 96 trips between 2021 and 2024. The results reveal substantial IEQ deficits, including elevated CO₂ concentrations, up to 5882 ppm in BRT buses, thermal discomfort (PMV-PPD values outside the -0.5 to +0.5 range in over 80 % of BRT trips), high pollutant levels on the PM2.5 exceeding 25 µg/m³ in most train trips, and noise exposure, driven by overcrowding, faulty HVAC systems, and suboptimal cabin design. This study proposed actionable strategies for enhancing indoor environmental quality (IEQ) in public vehicles, including ventilation approaches, cabin management, maintenance protocols, and public awareness campaigns. Recommendations also call for establishing localized IEQ regulations, implementing real-time monitoring systems, and promoting sustainable mobility initiatives and effective urban planning, including policy reforms. This study contributes to the limited literature on IEQ in tropical public transport vehicles (PTVs). It provides relevant insights for future frameworks that can enhance commuter experience and mitigate public health risks in similar or different contexts.